CORRELATION OF PROBLEM SOLVING ABILITY WITH LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION AND ETHICS SUBJECTS AT SMP NEGERI 2 KOLAKA - Andi Fani Pratiwi; Ahmad Tanaka; Akmir Akmir (Jurnal Teknologi Pendidikan Madrasah, 2024)
Education is not only a learning process, but developing the abilities and potential within students. With the growth of students' abilities, intelligence, and potential, every child has knowledge, is healthy both physically and mentally, has good abilities, can be independent, and can be responsible both for themselves and in society. This research uses a quantitative approach. A quantitative approach based on the philosophy of positivism, used to research on certain populations or samples, data collection using research instruments, data analysis is quantitative / statistical, with the aim of describing and testing predetermined hypotheses. From the results of this study, it can be seen that between probelm solving ability and learning outcomes in Islamic Religious Education and Budi Pekerti subjects there is a considerable correlation. To be able to give an interpretation of the strength of the relationship, it can be seen in the following table of Interpretation of the correlation coefficient value.